Pengaruh Pemberian Pupuk Organik Cair Air Cucian Beras dan Air Kelapa pada Budidaya Bayam Sistem Wick - Tedi Heryan; Ridwan Baharta; Rita Purwasih; Muhammad Gilang Ramadhan (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2022)
Hydroponics production of spinach required adequate plant nutrition such as AB mix solution. However due to its high price, an alternative source of nutrition such as liquid organic fertilizer (LOF) from rice washing water and coconut water has the potential to be the solution. The purpose of the final project was to determine the effect of adding liquid organic fertilizer of rice washing water and coconut water on the growth of spinach and to find the best concentration of liquid organic fertilizer. LOF physical characteristics (color, aroma, and pH) and their addition to the growth of spinach (plant height, number of leaves, measurement of nutrient concentration, fresh weight, and dry weight) were observed. This final project used a completely randomized design with 5 treatments and 3 replications. (P0: positive control (AB mix) 1%, P1: negative control (water), P2: 2%, P3: 4%, and P4: 6%). was analyzed ANOVA with a 5% level followed by DMRT. The results of liquid organic fertilizer of rice washing water and coconut water had Irish coffee color, distinctive aroma of Tape, and pH 4.6. The addition of LOF at 2% (P2) gave better results than P1 and gave significantly different results to plant height (16.17 cm), the number of leaves (9 strands), nutrient concentration (315 ppm), fresh weight (6.44 g), and dry weight (0.90 g).